Ice Pillars, Packwalls, and Brattices - David L. Kuck (International Conference on Ground Control in Mining, 1987)
This paper describes a system for providing structural, support in underground mines, employing water ice for pillars. packwalls and brattices. It consists of a refrigeration brine chiller, brine circulation system, and disposable plastic containers. The system provides for the timely freezing of uniform ice pillars, and for ice maintainance and/or melting on demand. Unique, useful ice properties include: expansion upon freezing, resilience to dynamic loads, and plasticity. Ice will not dilute or contaminate coal or ore. Economic advantages include: 1) lower labor and material costs (water can be piped to the ice pillar site through mine-water, spray-water, or drill-water lines); 2) replacement or supplementation of timber. concrete or other roof support equipment; and 3) potential use of ice brattices as ventillation control; and 4) conversion of ice bratices to ice pillars upon retreat. See Figure . A safety advantage for personnel and equipment is that ice pillars can be placed in hazardous sites, by remote control, if neccessary, without human entry. All filling, freezing and melting operations can be controlled from a safe distance.